STATUS OF MAMMAL POPULATIONS IN THE NATIONAL RESERVE MATSÉS, NORTHEAST OF THE PERUVIAN AMAZON - TORRES-OYARCE, León (2017)
This study was conducted between June and October 2015, in the Matsés National Reserve, with the objective of knowing the status of hunting mammal populations in three sampling sectors: Alemán, Loboyacu and Alto Gálvez. The data were collected in four linear transects, each one had 5 km. In the three sampling sectors, the primates had the highest population densities. In the Alto Gálvez sector, 2 the species with the highest density were Saimiri macrodon (26.75 ind / km ) and Sapajus macrocephalus 2 (18.93 ind / km ); while in the Aleman and Loboyacu sectors, it was Lagothrix lagotricha (23.54 and 13.84 2 2 ind / km , respectively) and Saguinus mystax (20.58 and 17.87 ind / km , respectively). In general, the variability of game mammals can be explained to 67.52%. Mammal communities of the Aleman and Loboyacu sectors were similar, where hunting was frequent. The independent comparison of both sectors versus the Alto Gálvez sector showed that the last sector had higher population densities. That is, the upper basin of the Gálvez River maintains the healthiest populations of mammals.